Microwave-assisted extraction of phenolic compounds and lutein from Nannochloropsis oceanica - Lay, Sovannmony (Animo Repository, 2021)
Nannochloropsis oceanica has been considered as a high source of carotenoids, lutein, and other phenolics--these compounds have been known to be beneficial for the prevention of many diseases. Therefore, this study investigated the extraction of lutein and total phenolic contents from Nannochloropsis oceanica by applying the microwave-assisted extraction (MAE) method. In the MAE process, the effect of various extraction parameters including ethanol concentrations (60-100 %) and temperatures (40-60 ) on total phenolic contents and lutein extraction yields, optimization of total phenolic extraction parameters by Response Surface Methodology (RSM) with Face-Centered Composite Design were studied. The result indicated that the temperature had no significant effect on the yield of total phenolic compounds, while the ethanol concentration had a negative significant effect on the yield of total phenolics. The yield of total phenolic content increased with increasing ethanol concentration. However, the yield of total phenolics decreased with further increase of ethanol concentration. Likewise, it was found that temperature strongly influenced the extraction yield of lutein. Increasing temperature led to a decrease in the yield of lutein which may be due to the degradation of lutein at high temperature (60 oC). However, it was observed that the extraction yield of lutein increased when pure ethanol was used for extraction. In this study, the optimum result by RSM with Face-Centered Composite Design showed that the optimum extraction condition of total phenolics from Nannochloropsis oceanica was at temperature 57 and ethanol concentration 74%. At this optimum condition, the yield of total phenolics was found to be 10.70 mg GAE/g sample.